Bilateral Avascular Necrosis of Femoral Heads Associated with Pregnancy: A Case Report and Review of Literature - KÜTÜK, EMİR; İĞREK, SERVET (GALENOS YAYINCILIK, 2018)
Avascular necrosis (AVN) is a pathological process that results in death of bone marrow cells and osteocytes after the disturbance of normal blood flow of the affected bone. AVN of the femoral head is a progressive disease that generally seen in the fourth through fifth decades of life. If it is not diagnosed and treated in the early period, it can lead to complete deterioration in the hip joint. It is estimated that 20.000 new cases have been diagnosed in the USA each year. The list of common causes for AVN includes alcohol consumption, gout, Caisson disease, Gaucher disease, renal osteodystrophy, hypercoagulable states, sickle cell anemia, systemic steroid use, and trauma. Hip AVN that occurs during or immediately after pregnancy is a quite rare condition and a limited number of cases have been reported in the literature until present time. Little is known about pregnancy as an etiological factor for femoral head AVN with a few cases in the literature. In this study, a 24-year-old female patient who developed AVN in her bilateral femoral head at the last trimester of pregnancy is presented.
Keywords: Avasculer necrosis; femoral head; pregnancy; OSTEONECROSIS